ANALISIS RASIO ASET DALAM MEMPREDIKSI PERKEMBANGANiPERBANKAN SYARIAHiDI INDONESIA PADA MASA COVID-19 - Alexander Yusuf Imaduddin Indra Surya; Faros Hafidz Muhammad Trizhadi; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The financial sector is very important for the progress of a country. The financial sector including sharia banking will help the economy indirectly, especially during the pandemic. The aim of this research is to evaluate the financial performance of Islamic banking in Indonesia during the COVID-19 pandemic. This research uses profitability ratios consisting of BOPO, ROA, ROE, liquidity ratios consisting of cash and FDR ratios, as well as solvency ratios calculated with the CAR ratio. This quantitative descriptive research measures a bank's financial performance using its profitability ratio level. This study found that bank performance scores changed during the COVID-19 pandemic. Bank performance based on profitability ratios shows that some Islamic banks are considered efficient, while others show a decline in performance. Several real industries affected by COVID-19.